Food- and diet-based validations of a Nestlé Nutrient Profiling System for reformulation in two nationally representative surveys. Issue 9 (24th October 2018) - Vieux, Florent; Privet, Lisa; Masset, Gabriel
Abstract: The Nestlé Nutritional Profiling System (NNPS) has been developed to guide food and beverage reformulation. The WHO published guidelines to develop and validate nutrient profiling systems. The objective was to conduct validation tests of the NNPS following principles of the WHO guidelines. French (Individual and National Survey on food Consumption 2006–2007) and the USA (National Health and Nutrition Examination Surveys 2011–2012) nationally representative dietary surveys were used. NNPS outcomes (PASS, FAIL, out-of-scope) of foods were compared with the validated UK Ofcom nutrient profiling system outcomes. Contributions of NNPS outcomes to energy intakes were compared between diets nutritional quality classes defined by two methods: based on a food-based quality indicator (Programme National Nutrition Santé Guideline Score in France, Healthy Eating Index 2010 in the USA) or on a combination of three nutrient-based indicators (mean adequacy ratio, mean excess ratio and energy density). In both countries, food items with a NNPS FAIL outcome had a lower nutritional quality according to the UK Ofcom, with an overall agreement between the two systems of 75·7 % in France and 68·8 % in the USA. In both countries, a high (respectively, low) contribution of NNPS PASS (respectively, NNPS FAIL) was positively associated with diet healthiness. Absolute associations were stronger between the contribution of NNPS FAIL products and measures of diet healthiness. Foods and beverages reaching NNPS standards appeared to have a higher nutritional quality and would be more likely to contribute to healthier diets, mainly linked to a reduction of nutrients to limit.